Longitudinal control laws design for a flying wing aircraft - Zhu, Yan. (Cranfield University, 2012)
This research is concerned with the flight dynamic, pitch flight control and flying qualities assessment for the reference BWB aircraft. It aims to develop the longitudinal control laws which could satisfy the flying and handing qualities over the whole flight envelope with added consideration of centre of gravity (CG) variation. In order to achieve this goal, both the longitudinal stability augmentation system (SAS) and autopilot control laws are studied in this thesis. Using the pole placement method, two sets of local Linear-Time-Invariant (LTI) SAS controllers are designed from the viewpoints of flying and handing qualities assessment and wind disturbance checking. The global gain schedule is developed with the scheduling variable of dynamic pressure to transfer gains smoothly between these two trim points. In addition, the poles movement of short period mode with the varying CG position are analysed, and some approaches of control system design to address the problem of reduced stability induced by CG variation are discussed as well. To achieve the command control for the aircraft, outer loop autopilot both pitch attitude hold and altitude hold are implemented by using the root locus method. By the existing criteria in MIL-F-8785C specifications being employed to assess the augmented aircraft response, the SAS linear controller with automatic changing gains effectively improve the stability characteristic for the reference BWB aircraft over the whole envelope. Hence, the augmented aircraft equals to a good characteristic controlled object for the outer loop or command path design, which guarantee the satisfactory performance of command control for the BWB aircraft. The flight control law for the longitudinal was completed with the SAS controller and autopilot design. In particular, the SAS was achieved with Level 1 flying and handing qualities, meanwhile the autopilot system was applied to obtain a satisfactory pitch attitude and altitude tracking performance.
Keywords: SAS Control Law; Flying and Handing Qualities; Gain Scheduling; Pitch Attitude Hold; Altitude Hold; Altitude Hold